PELAKSANAAN PENGAWASAN DINAS TATA RUANG DAN BANGUNAN KOTA PEKANBARU TERHADAP BANGUNAN YANG TIDAK MEMILIKI IZIN MENDIRIKAN BANGUNAN DI KECAMATAN TAMPAN - Irawan, Hengki; Tua, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Supervision of Building Permit (IMB) is an activity and effort to determine and assess the actual reality of the execution of the work or activity is in accordance with the plans and procedures or not. The problem in this research is how the implementation of supervision by the Department of Spatial Planning and Building Pekanbaru on building permits (building does not have permission), and the factors that triggered the building that does not have a license in the District of Pekanbaru City Handsome and obstacles in the implementation of supervision. The purpose of this study was to determine the extent of supervision by the Department of Spatial Planning and Building Pekanbaru to buildings that do not have the IMB.Researchers used the theoretical concept which adopted the theory of supervision by Manullang. The method used in this research is descriptive qualitative data collection instrument includes interviews with employees of the Department of Spatial control section and Pekanbaru City and community building, observation and document.The results of this study indicate that supervision Spatial Planning and Building Pekanbaru to buildings that do not have a building permit (IMB) in District Charming is not good. Factors that influence the lack of supervision of building permits and building permits violated ie, lack of personnel and operational vehicles to conduct a thorough supervision, lack of socialization, lack of public awareness, community economic factors, particularly the lower middle income people are the cause of reluctance in taking care of IMB before building.Keywords: Development, Monitoring, IMB.